Modern Interpretation of Root Canal Treatment and Modern Clinical Diagnostic Methods in Periodontitis - oʻgʻli, Elnazarov Azamat Toʻlqin (American Journal of Bioscience and Clinical Integrity, 2025)
Treatment of periodontal diseases with local drugs involves the use of agents that affect the etiological factors, pathogenetic mechanisms and symptoms of the disease. Dosage forms are dosed, methods of administration of drugs are adapted for local use. Drugs can be used in the form of rinses, irrigation, gum dressings and medical plates.